YATIM PIATU SEBAGAI MUSTAHIK ZAKAT PERSPEKTIF HUKUM ISLAM - An’im Fattach (Maliyah : Jurnal Hukum Bisnis Islam, 2016)
BAZ Duduk Sampeyan base used in determining orphaned as mustahik zakat in surah al-Ma'un and al-Maidah verse two is essentially a command to help each other live in developing Al-Birru that is good and worthwhile based on the enforcing piety to Allah and call for the community fully responsible for the handling of poverty as well as a warning to Muslims to not rebuke orphans, but should pay special attention so that does not include those who were negligent in religion and celebrate His grace. Determination of the orphaned as a charity is legitimate mustahik implemented because although not included among orphans entitled to receive zakat, but can be grouped into the class of indigent or poor, by reason of an orphan who lives in the village Dusuk Sampeyan situation is so concerned that deserve attention.